2020
DOI: 10.1039/d0sc04886k
|View full text |Cite
|
Sign up to set email alerts
|

The sporothriolides. A new biosynthetic family of fungal secondary metabolites

Abstract: The biosynthetic gene cluster of the antifungal metabolite sporothriolide 1 was identified from three producing ascomycetes: Hypomontagnella monticulosa MUCL 54604, H. spongiphila CLL 205 and H. submonticulosa DAOMC 242471. A...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 33 publications
4
34
1
Order By: Relevance
“…We, [20,21] and others, [22] have shown that reconstruction of cryptic fungal biosynthetic pathways in the host organism Aspergillus oryzae NSAR1 is an effective way to understand complex transformations. Here, we deploy those methods and in vitro studies of isolated enzymes aiming to overcome the hurdles that have previously hampered characterization of pathway intermediates during the biosynthesis of these intriguing metabolites [3] …”
Section: Introductionmentioning
confidence: 99%
“…We, [20,21] and others, [22] have shown that reconstruction of cryptic fungal biosynthetic pathways in the host organism Aspergillus oryzae NSAR1 is an effective way to understand complex transformations. Here, we deploy those methods and in vitro studies of isolated enzymes aiming to overcome the hurdles that have previously hampered characterization of pathway intermediates during the biosynthesis of these intriguing metabolites [3] …”
Section: Introductionmentioning
confidence: 99%
“…A separation by Supercritical Fluid Chromatography on chiral stationary phase allowed us the obtaining and characterization of the enantiomerically natural pure (+)-antipode. While we recently contributed to the elucidation of the biosynthesis pathway of the sporothriolide 1, [35] the biosynthesis of the trienylfuranol A 2 and sporochartines 3 remains to be elucidated, in particular the involvement of a Diels-Alder type reaction. We will benefit from the…”
mentioning
confidence: 99%
“…This release mechanism differs from that used by fungal FAS (e.g. SpoFas) 3 where the malonyl-palmitoyl transferase (MPT) domain is known to both load malonyl CoA extenders, and release products directly as CoA thiolesters. 38 The next step of the pathway is also closely related to primary metabolism.…”
Section: Discussionmentioning
confidence: 89%